The Importance of Digital Literacy in Geography Learning for Geography Education Students at Fish Unima - Hermon Mauritis Karwur; Xaverius E. Lobja; Yunike Sulistyosari; Manuel E Korompis (Technium Social Sciences Journal, 2023)
The formulation of the research problem is how digital literacy ability in geography learning for students majoring in geography education at FISH Unima. The study aimed to determine digital literacy abilities in geography learning for FISH Unima geography education students. In achieving these objectives, this research was carried out using qualitative research methods, and data collection techniques which included: observation, interviews, documentation, and triangulation. The research informants were FISH Unima geography education students. The stages of data analysis include data reduction, data display, and conclusion drawing/verification. The results showed that results of the study showed that there were several digital literacy skills among students of FISH Unima geography education, namely: a) the ability to obtain various information needed in learning, b) the ability to use the internet, c) the ability to recognize computers as a means and technology in learning, d) the ability to use various digital media and e) the ability to understand sources as learning materials.